Autosomal dominant form of type IV collagen nephropathy exists among patients with hereditary nephritis difficult to diagnose clinicopathologically - Imafuku, Aya (Nephrology (Carlton), 2018)
AIM: Type IV collagen nephropathies include Alport Syndrome and thin basement membrane nephropathy (TBMN), which are caused by mutations in COL4A3/A4/A5 genes. Recently, reports of patients with heterozygous mutations in COL4A3/A4 have been increasing. The clinical course of these patients has a wide variety, and they are diagnosed as TBMN, autosomal dominant Alport syndrome (ADAS), or familial focal segmental glomerular sclerosis. However, diagnosis, frequency and clinicopathological manifestation of them remains unclear. We tested COL4A3/A4/A5 genes in patients with hereditary nephritis that was difficult to diagnose clinicopathologically, and investigated who should undergo such testing. METHODS: We performed immunostaining for α5 chain of type IV collagen [α5 (IV)] in 27 patients from 21 families who fitted the following criteria: (i) haematuria and proteinuria (± renal dysfunction); (ii) family history of haematuria, proteinuria, and/or renal dysfunction (autosomal dominant inheritance); (iii) no specific glomerulonephritis; and (iv) thinning, splitting, or lamellation of the glomerular basement membrane (GBM) on electron microscopy. Then we performed genetic testing in 19 patients from 16 families who showed normal α5 (IV) patterns. We conducted a retrospective analysis of their clinicopathological findings. RESULTS: Among 16 families, 69% were detected heterozygous mutations in COL4A3/A4, suggesting the diagnosis of TBMN/ADAS. Twenty‐one percent of patients developed end stage renal disease. All patients showed thinning of GBM, which was accompanied by splitting or lamellation in seven patients. CONCLUSION: A considerable fraction of patients with hereditary nephritis that is difficult to diagnose clinicopathologically have TBMN/ADAS. It is important to recognize TBMN/ADAS and perform genetic testing in appropriate patients.